2013
DOI: 10.1021/ie302972k
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study on the Effect of Water on the Carbonation of Portlandite

Abstract: Hardening of lime-based binders is a process where carbonation of portlandite plays an important role. Additionally, carbonation of hydrated lime is of general technical interest, e.g., for carbon dioxide capture. The mechanisms responsible for this reaction are not well-known. In this work, we study the carbonation of portlandite without water and with one water molecule at atomistic scale. Density functional theory (DFT) is used to simulate the reaction path and to accurately calculate minima and transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…As it was explained in literature, 39,40 carbonates are formed through different kind of processes. The first mechanism is the diffusion of CO 2 into the empty pores of the surface where it will react with water from the pore solution, forming carbonic acid.…”
Section: Resultsmentioning
confidence: 96%
“…As it was explained in literature, 39,40 carbonates are formed through different kind of processes. The first mechanism is the diffusion of CO 2 into the empty pores of the surface where it will react with water from the pore solution, forming carbonic acid.…”
Section: Resultsmentioning
confidence: 96%
“…Formation of solid calcium carbonates results from the reaction of free Ca 2+ ions and CO 3 −2 carbonate ions. 38 The reaction is strongly influenced by the chemical potential of water in the environment. The adsorption of CO 2 on CaSiO 3 with a water monolayer completely changes its mechanism.…”
Section: ■ Resultsmentioning
confidence: 99%
“…This implies that fully hydroxylated surfaces suppress the formation of carbonate ions, hence, a higher reactivity barrier for CO 2 with the (001) surface in comparison to the (100) and (110) surfaces. Indeed, the probability of carbonation of the (001) surface in solid-state form has been reported to be very low under ambient conditions [28] and experimental results have indicated that almost no carbonation occurs in the absence of water [73,79].…”
Section: Structural and Dynamical Analysis Of Scco2 Within Portlandite Poresmentioning
confidence: 99%
“…Nevertheless, due to the complexity of the subsurface environmental conditions, it is difficult to experimentally disentangle various factors controlling the carbonation of wellbore cement. In this regard, atomistic computer simulation approaches have proven to be very useful because of their ability to provide atomic-scale quantitative information about the physical and chemical processes occurring during carbonation [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation